A short excursion into the energy supply mix in Nigeria (2012)
Abundant energy supply is the lifeblood of modern civilization. Energy poverty arising from poor management despite appreciable energy resource base continues to be a major constraint on the socio-economic development of Nigeria. The crucial challenge of the energy sector in the country includes inadequate energy supply, its security and sustainability. In this paper we briefly examine the roles of the major primary energy forms in the country as well as some of the alternative energy sources in the provision of adequate energy supply to meet the growing demand. The paper posits that poor energy mix, slow implementation of policies and inadequate private sector participation are the major constraints and challenges of the energy sector. Concerted efforts towards addressing these challenges will go a long way in solving the endemic energy problem in the country.